In mathematics , Lady Windermere's Fan is a telescopic identity employed to relate global and local error of a numerical algorithm . The name is derived from Oscar Wilde 's 1892 play Lady Windermere's Fan, A Play About a Good Woman .
Lady Windermere's Fan for a function of one variable
Let
E
(
τ
,
t
0
,
y
(
t
0
)
)
{\displaystyle E(\ \tau ,t_{0},y(t_{0})\ )}
be the exact solution operator so that:
y
(
t
0
+
τ
)
=
E
(
τ
,
t
0
,
y
(
t
0
)
)
y
(
t
0
)
{\displaystyle y(t_{0}+\tau )=E(\tau ,t_{0},y(t_{0}))\ y(t_{0})}
with
t
0
{\displaystyle t_{0}}
denoting the initial time and
y
(
t
)
{\displaystyle y(t)}
the function to be approximated with a given
y
(
t
0
)
{\displaystyle y(t_{0})}
.
Further let
y
n
{\displaystyle y_{n}}
,
n
∈
N
,
n
≤
N
{\displaystyle n\in \mathbb {N} ,\ n\leq N}
be the numerical approximation at time
t
n
{\displaystyle t_{n}}
,
t
0
<
t
n
≤
T
=
t
N
{\displaystyle t_{0}<t_{n}\leq T=t_{N}}
.
y
n
{\displaystyle y_{n}}
can be attained by means of the approximation operator
Φ
(
h
n
,
t
n
,
y
(
t
n
)
)
{\displaystyle \Phi (\ h_{n},t_{n},y(t_{n})\ )}
so that:
y
n
=
Φ
(
h
n
−
1
,
t
n
−
1
,
y
(
t
n
−
1
)
)
y
n
−
1
{\displaystyle y_{n}=\Phi (\ h_{n-1},t_{n-1},y(t_{n-1})\ )\ y_{n-1}\quad }
with
h
n
=
t
n
+
1
−
t
n
{\displaystyle h_{n}=t_{n+1}-t_{n}}
The approximation operator represents the numerical scheme used. For a simple explicit forward Euler method with step width
h
{\displaystyle h}
this would be:
Φ
Euler
(
h
,
t
n
−
1
,
y
(
t
n
−
1
)
)
y
n
−
1
=
(
1
+
h
d
d
t
)
y
n
−
1
{\displaystyle \Phi _{\text{Euler}}(\ h,t_{n-1},y(t_{n-1})\ )\ y_{n-1}=(1+h{\frac {d}{dt}})\ y_{n-1}}
The local error
d
n
{\displaystyle d_{n}}
is then given by:
d
n
:=
D
(
h
n
−
1
,
t
n
−
1
,
y
(
t
n
−
1
)
)
y
n
−
1
:=
[
Φ
(
h
n
−
1
,
t
n
−
1
,
y
(
t
n
−
1
)
)
−
E
(
h
n
−
1
,
t
n
−
1
,
y
(
t
n
−
1
)
)
]
y
n
−
1
{\displaystyle d_{n}:=D(\ h_{n-1},t_{n-1},y(t_{n-1})\ )\ y_{n-1}:=\left\ y_{n-1}}
In abbreviation we write:
Φ
(
h
n
)
:=
Φ
(
h
n
,
t
n
,
y
(
t
n
)
)
{\displaystyle \Phi (h_{n}):=\Phi (\ h_{n},t_{n},y(t_{n})\ )}
E
(
h
n
)
:=
E
(
h
n
,
t
n
,
y
(
t
n
)
)
{\displaystyle E(h_{n}):=E(\ h_{n},t_{n},y(t_{n})\ )}
D
(
h
n
)
:=
D
(
h
n
,
t
n
,
y
(
t
n
)
)
{\displaystyle D(h_{n}):=D(\ h_{n},t_{n},y(t_{n})\ )}
Then Lady Windermere's Fan for a function of a single variable
t
{\displaystyle t}
writes as:
y
N
−
y
(
t
N
)
=
∏
j
=
0
N
−
1
Φ
(
h
j
)
(
y
0
−
y
(
t
0
)
)
+
∑
n
=
1
N
∏
j
=
n
N
−
1
Φ
(
h
j
)
d
n
{\displaystyle y_{N}-y(t_{N})=\prod _{j=0}^{N-1}\Phi (h_{j})\ (y_{0}-y(t_{0}))+\sum _{n=1}^{N}\ \prod _{j=n}^{N-1}\Phi (h_{j})\ d_{n}}
with a global error of
y
N
−
y
(
t
N
)
{\displaystyle y_{N}-y(t_{N})}
Explanation
y
N
−
y
(
t
N
)
=
y
N
−
∏
j
=
0
N
−
1
Φ
(
h
j
)
y
(
t
0
)
+
∏
j
=
0
N
−
1
Φ
(
h
j
)
y
(
t
0
)
⏟
=
0
−
y
(
t
N
)
=
y
N
−
∏
j
=
0
N
−
1
Φ
(
h
j
)
y
(
t
0
)
+
∑
n
=
0
N
−
1
∏
j
=
n
N
−
1
Φ
(
h
j
)
y
(
t
n
)
−
∑
n
=
1
N
∏
j
=
n
N
−
1
Φ
(
h
j
)
y
(
t
n
)
⏟
=
∏
j
=
0
N
−
1
Φ
(
h
j
)
y
(
t
0
)
−
∑
n
=
N
N
[
∏
j
=
n
N
−
1
Φ
(
h
j
)
]
y
(
t
n
)
=
∏
j
=
0
N
−
1
Φ
(
h
j
)
y
(
t
0
)
−
y
(
t
N
)
=
∏
j
=
0
N
−
1
Φ
(
h
j
)
y
0
−
∏
j
=
0
N
−
1
Φ
(
h
j
)
y
(
t
0
)
+
∑
n
=
1
N
∏
j
=
n
−
1
N
−
1
Φ
(
h
j
)
y
(
t
n
−
1
)
−
∑
n
=
1
N
∏
j
=
n
N
−
1
Φ
(
h
j
)
y
(
t
n
)
=
∏
j
=
0
N
−
1
Φ
(
h
j
)
(
y
0
−
y
(
t
0
)
)
+
∑
n
=
1
N
∏
j
=
n
N
−
1
Φ
(
h
j
)
[
Φ
(
h
n
−
1
)
−
E
(
h
n
−
1
)
]
y
(
t
n
−
1
)
=
∏
j
=
0
N
−
1
Φ
(
h
j
)
(
y
0
−
y
(
t
0
)
)
+
∑
n
=
1
N
∏
j
=
n
N
−
1
Φ
(
h
j
)
d
n
{\displaystyle {\begin{aligned}y_{N}-y(t_{N})&{}=y_{N}-\underbrace {\prod _{j=0}^{N-1}\Phi (h_{j})\ y(t_{0})+\prod _{j=0}^{N-1}\Phi (h_{j})\ y(t_{0})} _{=0}-y(t_{N})\\&{}=y_{N}-\prod _{j=0}^{N-1}\Phi (h_{j})\ y(t_{0})+\underbrace {\sum _{n=0}^{N-1}\ \prod _{j=n}^{N-1}\Phi (h_{j})\ y(t_{n})-\sum _{n=1}^{N}\ \prod _{j=n}^{N-1}\Phi (h_{j})\ y(t_{n})} _{=\prod _{j=0}^{N-1}\Phi (h_{j})\ y(t_{0})-\sum _{n=N}^{N}\left\ y(t_{n})=\prod _{j=0}^{N-1}\Phi (h_{j})\ y(t_{0})-y(t_{N})}\\&{}=\prod _{j=0}^{N-1}\Phi (h_{j})\ y_{0}-\prod _{j=0}^{N-1}\Phi (h_{j})\ y(t_{0})+\sum _{n=1}^{N}\ \prod _{j=n-1}^{N-1}\Phi (h_{j})\ y(t_{n-1})-\sum _{n=1}^{N}\ \prod _{j=n}^{N-1}\Phi (h_{j})\ y(t_{n})\\&{}=\prod _{j=0}^{N-1}\Phi (h_{j})\ (y_{0}-y(t_{0}))+\sum _{n=1}^{N}\ \prod _{j=n}^{N-1}\Phi (h_{j})\left\ y(t_{n-1})\\&{}=\prod _{j=0}^{N-1}\Phi (h_{j})\ (y_{0}-y(t_{0}))+\sum _{n=1}^{N}\ \prod _{j=n}^{N-1}\Phi (h_{j})\ d_{n}\end{aligned}}}
See also
Category :
Text is available under the Creative Commons Attribution-ShareAlike License. Additional terms may apply.
**DISCLAIMER** We are not affiliated with Wikipedia, and Cloudflare.
The information presented on this site is for general informational purposes only and does not constitute medical advice.
You should always have a personal consultation with a healthcare professional before making changes to your diet, medication, or exercise routine.
AI helps with the correspondence in our chat.
We participate in an affiliate program. If you buy something through a link, we may earn a commission 💕
↑